Dana Desa Dan Tingkat Kemiskinan Di Kabupaten Banjar - Rosalina, Dewi Indah; Nuryadin, Muhammad Rusmin (PPJP ULM, 2022)
This study aims to determine the effect of village funds on reducing the number of poor people in Banjar Regency and how government policies reduce the number of poor people. This research is included in a mixed type of research, namely quantitative and qualitative research with the object of research being village funds in 19 Districts of Banjar Regency in 2018-2020 and as the independent variable (x) and the poverty level as the dependent variable (y) namely the number of poor people in 19 Districts of the Regency. Banjar 2018-2020. As an analytical material to examine more deeply, interviews were conducted with several Village Heads and the Banjar Regency PMD Service. The analytical method used in this study is simple regression of panel data with a fixed effect model. The results of this study indicate that village funds have no significant effect on reducing the number of poor people in Banjar Regency, however, based on the results of interviews, with the policies that have been implemented, village funds have an effect on reducing the number of poor people, although the effect is still very small.